Aspidistra shimentaiensis (Asparagaceae), a new species from Guangdong, China - Peng, Cai-Xia; Dai, Ke-Yuan; Li, Yuan-Qiu; Tong, Yi-Hua; Lin, Chun-Rui (Phytotaxa, 2023)
Aspidistra shimentaiensis, a new species of Asparagaceae from Guangdong, southern China, is described and illustrated. The new species is similar to A. nankunshanensis, but differs by the narrowly lanceolate leaf blade, purplish red pistil, slightly convex upper surface of stigma with a white triangular speckle and three inconspicuous Y-shaped wavy lines at center. Colour plates of the two similar species are provided for comparison.